THE IMPACT OF JOB SATISFACTION AND EMPLOYEE ENGAGEMENT ON EMPLOYEE RETENTION AT PT.MEGAH PRIMA SUPRA MAKMUR MANADO - Hido, Esterlita Claudia; Worang, Frederik G.; Saerang, Regina T. (Universitas Sam Ratulangi, 2021)
In era 4.0, Human resources are very important for increasing the profitability of one organization or company. Employees are not effective in working if they do not feel irresponsible and has a negative or positive impact on their of work. If they can not maintain a negative perception or negative development, of course, they can not reach the target or goals and surely the company will give a punishment. With so, confidence and optimism in the company will encourage employees to have a higher sense of attachment and make employees will stay and survive in the company.States According to Gary Dessler, â€œHuman resource management is the process of acquiring, training, appraising and compensating employees and of attending to their labor relations, health & safety and fairness concerns and how to obtain the job satisfaction for represents a personâ€™s evaluation of his or her job and works context. every organization must try to maximize the contribution of each employee to achieve success, each employee needs to find their work goals and satisfaction based on employee engagement and employee retention itself.Â Keywords: Job Satisfaction, Employee Engagement, and Employee Retention